Unification of Foreign Exchange Markets and Economic Growth - Ololade Sikiru ONIYIDE; Ebere P. IFIONU; Godfrey O. OMOJEFE (Research Parks Publishers, 2024)
This research study delves into the intricate relationship between exchange rate unification and its implications for economic stability, with a specific focus on the Nigerian context. Exchange rate unification, the process of transitioning from multiple exchange rate systems to a single unified rate, holds the potential to reshape an economy's dynamics, affecting investor confidence, trade balances, and overall macroeconomic stability. Through a comprehensive examination of pre-unification and post-unification exchange rate data and gross domestic product data, this research uncovers patterns in currency valuation, volatility, and investor sentiment. The study employed secondary data gotten from the Central Bank of Nigeria statistical bulletin. The study explores the changes in the mean and variability of exchange rates, highlighting shifts in currency dynamics after the unification process. The study found that there are variations in the pre and post-unification era which has economic effect potentials. Also, the study evaluated the quarterly trend of GDP from the first quarter of 2022 to the first quarter of 2023. The result exhibits a mixed trend across various sectors, with the influence of the exchange rate unification potentially being a key driver in shaping these trends in 2023. The impact of unification on currency stabilization, international trade, and investor confidence may have contributed to the overall growth trend. The study recommends renewed exchange rate management strategies, investor communication approaches, export diversification tactics, fiscal resilience planning, and risk management techniques for businesses.